Co-interventions with Clostridium butyricum and soluble dietary fiber targeting the gut microbiota improve MAFLD via the Acly/Nrf2/NF-κB signaling pathway. Issue 10 (11th May 2022) - Shao, Junwei; Ge, Tiantian; Wei, Yingliang; Zhou, Yuhan; Shi, Mengyuan; Liu, Huiyuan; Chen, Zhi; Xia, Yang
Abstract : Mechanisms of co-intervention with  Clostridium butyricum  and soluble dietary fiber to improve MAFLD. Abstract : Purpose : The pathogenesis of metabolic associated fatty liver disease (MAFLD) is complex. Lipid metabolic disorder, chronic inflammation, and oxidative stress are the core events for MAFLD. Dietary intervention is an important treatment strategy for preventing the onset and progression of MAFLD. Clostridium butyricum (CB) and soluble dietary fiber (SDF) are often considered beneficial for health. We explored how two microbiota-targeted interventions (SDF and CB) influence the hepatic immune system, oxidative stress, and lipid metabolism in MAFLD mice. Methods : To explore the role of SDF and CB in MAFLD, we generated MAFLD mouse models by feeding C57BL/6 mice with a high-fat diet (HFD). After 8 weeks of intervention, we measured immune cell function, lipid metabolism, and oxidative stress levels in the livers of mice. Results : Single intervention with SDF or CB was not effective in improving MAFLD; however, co-interventions with SDF and CB increased microbiota diversity and decreased inflammation, oxidative stress, and lipid synthesis. Moreover, we determined that co-intervention with SDF and CB mediated fatty acid oxidation by activating the Acly/Nrf2/NF-κB signaling pathway. Most importantly, co-intervention exerted anti-inflammatory effects by inhibiting the differentiation of macrophages into pro-inflammatory M1 macrophages. Conclusion : This study show that co-intervention with SDF and CB can improve MAFLD, and co-intervention with  SDF and CB are suggested to be potential gut microbiota modulators and therapeutic substances for MAFLD.